Analysis of Livelihood Security of Households: A Case Study from Rural Areas of Bundelkhand - Gautam, Pawan Kumar; Jha, Sujeet Kumar (Indian Journal of Extension Education, 2022)
Livelihood security is defined as securing the possession or access to income generating assets and activities, including reserves and assets, to the offsets. The study was conducted from 2018-19 to 2020-21 in Bundelkhand, which includes Uttar Pradesh (7 districts) and Madhya Pradesh (6 districts). Based on the broad literature assessment and discussion with experts, indicators were developed to measure dairy farmer livelihoods. Information was collected by personal interviews using a structured interview schedule. The survey found that the majority of smallholder farmers earn a low to moderate income. The average livelihood security index for marginal farmers was 0.55, and the average livelihood security index for middle-class farmers was 0.57. Education, land ownership, annual income, milk sales, and extension contacts had highly significant positive relationships with livelihood security.
Keywords: Livelihood; Dairy; Bundelkhand; Security; Social; Food